Quantifiers in Action Generalized Quantification in Query, Logical and Natural Languages - Badia, Antonio (Advances in Database Systems, 2009)
The database industry is clearly a multi-billion, world-wide, all-encompassing part of the software world. This is part thanks to the standardization of query languages in the form of SQL. And yet, it is well known that SQL has significant shortcomings. Quantifiers in Action: Generalized Quantification in Query, Logical and Natural Languages analyzes one of those shortcomings, the way in which quantification is dealt with in SQL. It is well known that most query languages are simply versions of First Order Logic (FOL). GQs are an extension of the idea of quantifier in FOL. Hence, GQs can be a meaningful extension of the treatment of quantification in query languages. Even though studied within the theoretical community up until now, GQs can be successfully applied, and are a perfect example of a practical theory within databases. This book provides a brief background in logic and introduces the concept of GQs, and then develops a query language based on GQs, called QLGQ. Using QLGQ, the reader explores the efficient implementation of the concept, always a primary consideration in databases. This professional book also includes several extensions, for use with documents employing question and answer techniques. Quantifiers in Action: Generalized Quantification in Query, Logical and Natural Languages is the result of several years of research funded by NSF through a CAREER Award. It is designed for practitioners and researchers that work within the database management field. This volume is also suitable for graduate-level students in computer science.